The Role of Social Network Theory and Knowledge-Based View in the Innovation Generation Process of a Supply Chain of Thai Agriculture Supply Chain - Anchalee Hiranphaet; Tommanee Sooksai; Kraiwit Sinthukhammoon; Sutas Jaepho (International Journal of Supply Chain Management, 2020)
The main objective of the current study is to investigate the role of social network theory and knowledge-based view in the innovation generation process of a supply chain of Thai Agriculture supply. By drawing on knowledge-based view we have found the three different aspects of a firm which can affect the process of innovation generation, customer–supplier exchange relationship especially environmental, technological and organizational factors that affect the innovation. Secondly, we will examine innovation generation empirically and its link with supplier–customer relationship performance which is still ambiguous issue. Thirdly we will check the moderation effect of supplier’s dependence on association among the drivers of innovation generation and the result of customer supplier relationship performance. The study found that the social capital  network position of the agriculture in Thailand  firm can be affected with a unit assessment of new knowledge which is dangerous for the development of new products According to the findings  lodging a good position in the network has additional power its more likely to achieve desired planned resources like knowledge and information. Therefore, we suppose that relationship among innovation drivers and output performance will be formed in the context of supplier who is depending on customers-supplier association.